Perfil de fatores de virulência das Escherichia coli isoladas do útero de vacas holandesas após o parto e sua relação com a microbiota uterina - Bicudo, Luana de Cássia [UNESP] (2014)
Bacterial contamination of the uterus after delivery is almost an unanimous event in cows, in which the Escherichia coli (E. coli) is the main micro-organism found. Despite this, the activation of local and systemic defense mechanisms gradually eliminate contaminants throughout the physiological puerperium. However, some bacterias possess virulence factors that facilitate its installation and remain in the host tissue, leading to the development of uterine infections. Although the mechanism is not fully elucidated, it is certified that, the presence of E. coli in the first days postpartum favors the growth of Trueperella pyogenes in a later period, bacteria often associated with uterine infection. Thus, aimed to establish the dynamics and profile of uterine microbiota relating the virulence factors of E. coli isolated from the uterus of cows 24 hours after calving, with the bacterial presence in the uterine environment in the second postnatal week. The study was conducted on 75 Holstein cows with normal delivery and postpartum without complications. After 24 hours of parturition (Moment 1), gynecological evaluation was performed by rectal palpation, observed staining of the vaginal mucosa and measurement of rectal temperature. Samples of secretion loquial were collected aseptically of these animals, aiming the microbiological culture, antibiogram and uterine cytology. The postpartum period was uneventful and monitored for changes in the reproductive and productive sphere. On the 14th day postpartum (Time 2), the same procedures were were performed, apart from transrectal ultrasonography. Blood samples were collected at both moments, to characterize the phagocytic ability of neutrophils by the nitroblue tetrazolium test (NBT) stimulated (S) and unstimulated (US) and hemogram. In E. coli isolates were investigated different genes associated with virulence factors (VF) by PCR. Rapid uterine involution, characterized by diameter of the ...